Nasaan si Francis - Fernandez, Gabby; Unico Entertainment (Unico Entertainment, 2006)
Boy (Paolo Contis) is a middle-class young man in desperate need of money to save his girlfriend who is being forced to work as a prostitute under the town's powerful Mama San. To solve his problem he decides to pawn off a carabao to his ex-partner in crime and childhood friend Sonny (Rico Blanco), he asks his wealthy but violent friend for help. Instead of taking his offer, Francis counters with a different deal - he consigns them 50 tablets of ecstasy that they can sell for double the price and thereby raising the money Boy needs. Francis invites them to smoke up to seal the deal. Francis goes into cardiac arrest and dies. The two try to revive him but eventually give up. Instead of informing the authorities or Francis' family, they decide to hide the body until they find the 50 tables. What ensure is a hilarious cat-and-mouse game throughout the house and around the deeper issues of family, friendship, etc.